Altered circRNAs: a novel potential mechanism for the functions of extracellular vesicles derived from platelet-rich plasma - Niu, Lifeng; Wang, Yanli; Gao, Yao; Zhang, Jun (Frontiers in Bioinformatics, 2026)
Platelet-rich plasma (PRP) has been widely applied in clinical practice for tissue repair and regeneration. Recent studies have reported that large amounts of extracellular vesicles (EVs) derived from PRP (PRP-EVs) are also involved in the functions of tissue repair and regeneration, except for the secreted growth factors. However, the relevant mechanisms of PRP-EVs remain unknown. In this study, we attempted to reveal the potential circular RNA (circRNA) mechanisms of PRP-EVs using high-throughput RNA sequencing (RNA-seq) technique and bioinformatics analysis. Six healthy donors were enrolled in this study, including three donors for the isolation of PRP-EVs and three donors for the isolation of EVs derived from blood plasma (plasma-EVs). As a result, we confirmed that PRP activation by thrombin could significantly promote the formation and secretion of EVs, particularly those with diameters ranging from 50 to 200 nm. Moreover, 144 circRNAs were altered in PRP-EVs with a fold change ≥ 2.0 and p-value ≤ 0.05. Among these, 89 circRNAs were upregulated, whereas 55 circRNAs were downregulated. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway, and circRNA–miRNA–mRNA interaction network analyses were performed to predict the potential roles of circRNAs in PRP-EVs. GO analysis indicated that these altered circRNAs might be related to the physiological processes of cell genesis and development. The pathways that were most strongly correlated with the biological functions of PRP-EVs were the transforming growth factor β (TGF-β) signaling pathway and HIF-1 signaling pathway. In addition, the expression levels of five selected circRNAs were verified through RT-qPCR. In conclusion, this is the first study to explain a novel potential mechanism of the biological functions of PRP-EVs in terms of the altered circRNAs. Taken together, our findings in this study may lay the groundwork for the clinical application of PRP-EVs and provide possible novel targets for further research.